Rancang Bangun Mesin Hot Press Particle Board Sekam Padi Berbasis Pnaumatik - Sifa, Agus; Mahfud; M. Selin; Badruzzaman (Journal of Applied Mechanical Technology, 2024)
Rice husk waste, often produced by the rice milling industry, creates a problem. To utilize rice husk waste, one of the uses is to make a product in the form of particle board by heating and pressing with a hot press machine. This study aims to design and build a hot press machine to make a rice husk particle board with a press using a pneumatic system. The method for making a hot press machine is by making a machine design, load calculations, and static simulations on the frame, then manufacturing using a fabrication and assembly process. The results of the design and manufacture were obtained with machine dimensions of 1372x800x700mm, maximum heating temperature of 175oC, a pneumatic system using two double-acting actuators, von Misses stress results from an even load of 143 N on the frame, obtained a von Misses stress of at least 2.405e-1N/m2 and The maximum Von Misses Stress of 1.856e6N/m2is still a safe limit because above the yield strength value of the material used, the maximum displacement value is 1.098 mm. The safety factor is 2.01.